1986
DOI: 10.1017/s0195941700064626
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial Infections in 15 Rural Wisconsin Hospitals—Results and Conclusions from 6 Months of Comprehensive Surveillance

Abstract: Fifteen rural Wisconsin acute care community hospitals with an average approved bed size of 55 and an average daily census of 28 patients participated in a nosocomial infection control project. Each hospital Infection Control Practitioner (ICP) was trained and conducted prospective nosocomial infection surveillance on all patients admitted to the hospital for 6 consecutive months between May 1,1984 and April 30, 1985. Two hundred twenty nosocomial infections were reported among 13,420 discharged patients for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…However, the study by Scheckler and Peterson 15 showed that, in rural Wisconsin hospitals with a low surgical volume, the incidence of SSI also was low. That study showed that lower hospital and surgeon volumes were associated with a higher incidence of SSI among those patients undergoing CABG, as noted in previous reports.…”
Section: Discussionmentioning
confidence: 98%
“…However, the study by Scheckler and Peterson 15 showed that, in rural Wisconsin hospitals with a low surgical volume, the incidence of SSI also was low. That study showed that lower hospital and surgeon volumes were associated with a higher incidence of SSI among those patients undergoing CABG, as noted in previous reports.…”
Section: Discussionmentioning
confidence: 98%
“…Rates have varied from 6 to 40 per 100 admissions in the NICU, [18][19][20][21] and this compares with a rate of approximately 0.3 to 1.7 per 100 admissions in normal newborn nursery. 20,22 Rates of health care-associated infections in the NICU are higher in lower birth weight infants, with the rates being nearly 3 times higher in infants whose birth weights are ,1500 grams compared with those with a birth weight of .1500 grams. In addition, health careassociated infection rates are higher in units that include neonatal surgical patients and in units that include nosocomial viral infections 20 in their surveillance data.…”
Section: Epidemiology and Transmissionmentioning
confidence: 99%